THE ROLE OF AUTOLOGOUS HAMSTRING GRAFT IN IMPROVING FUNCTIONAL OUTCOME AFTER ARTHROSCOPIC ANTERIOR CRUCIATE LIGAMENT RECONSTRUCTION: PROSPECTIVE STUDY AT GGH, KURNOOL - babu, pasupuleti archana; Priyanka (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The prevalence of knee ligament injuries is on the rise due to increasing engagement in sports activities. Among the various ligaments present in the knee joint, the anterior cruciate ligament (ACL) is the most commonly injured. Several procedures have been described for the reconstruction of a torn ACL, ranging from open to arthroscopic techniques. In this particular study, we utilized an autograft from the hamstring muscle for ACL reconstruction. The graft was secured with an Endobutton on the femoral end and an interference screw at the tibial end. If necessary, cancellous screws or a suture wheel was used as well. Methods: This is a 2-year prospective study conducted between April 2021 and March 2023 at GGH, Kurnool, which included 20 cases of complete ACL tear. All patients underwent arthroscopic ACL reconstruction using a hamstring graft. Following the procedure, all patients were assessed using the lysholm knee scoring questionnaire and were monitored at specific intervals, including 3 months, 6 months, and 1 year, to evaluate their progress. Results: After 1 year, the lysholm knee scoring questionnaire was used to evaluate the results of the ACL reconstruction with the hamstring graft. The findings revealed that 30% (6 cases) of the cases reported excellent results, 50% (10 cases) of the cases showed good results, 15% (3 cases) of the cases showed fair results, and 5% (1 case) of the cases obtained poor results. In addition, 80% of patients achieved functional restoration to their pre-injury level. At 1-year follow-up, our study found that the average pre-operative lysholm score was 63.24, while the average post-operative score was 91.98, which showed a statistically significant improvement in the post-operative lysholm score compared to the pre-operative score (p<0.05). Conclusions: Our study suggests that the use of a hamstring graft for the reconstruction of a torn ACL can result in excellent to good outcomes. However, it should be noted that proper patient selection and physiotherapy play a significant role in achieving favorable results.